Unsteady natural convection with entropy generation in partially open triangular cavities with a local heat source - Öztop, Hakan Fehmi; Bondareva, Nadezhda S.; Sheremet, Mikhail A.; Abu-Hamdeh, Nidal (Emerald Group Publishing Ltd, 2017)
Purpose - The main aim of this work is to perform a numerical analysis on natural convection with entropy generation in a partially open triangular cavity with a local heat source. Design/methodology/approach - The unsteady governing dimensionless partial differential equations with corresponding initially and boundary conditions were numerically solved by the finite difference method of the second-order accuracy. The effects of dimensionless time is studied, and other governing parameters are Rayleigh number (Ra = 10(3) - 10(5)), Prandtl number (Pr = 6.82), heater length (w/L = 0.2, 0.4 and 0.6) and distance of heater ratio (delta/L = 0.3). Findings - An increase in the Rayleigh number leads to an increment of the fluid flow and heat transfer rates. Average Bejan number decreases with Ra as opposed to the average Nusselt number and average entropy generation. High values of Ra characterize a formation of long-duration oscillating behavior for the average Nusselt number and entropy generation. Originality/value - The originality of this work is to analyze the entropy generation in natural convection in a one side open and partial heater-located cavity. This is a good application for electronical systems or building design.
Keywords: Numerical results; Natural convection; Local heat source; Partially open triangular cavity; Unsteady regimes